PENGARUH CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE DENGAN MEDIASI LIKUIDITAS PADA PERUSAHAAN BUMN YANG TERDAPAT DI BEI TAHUN 2017-2019 - Manurung, Vio Lolyta; Hutabarat, Francis (Universitas Sam Ratulangi, 2020)
The aims of this study is to test the effect of corporate governance on tax avoidance by using liquidity as a mediation in state-owned companies (BUMN) that have been listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period. This study uses descriptive analysis theory and processing is carried out in SPSS software. There are 20 state-owned companies (BUMN) listed on the Indonesia Stock Exchange (BEI) for the 2017-2019 period which were used as samples in this study. This study uses tax avoidance which functions as the dependent variable and uses corporate governance which functions as an independent variable and is assisted by using liquidity as a mediating variable. In addition, descriptive statistics, F test, and t test were also used in this study as statistical analysis. The results of the analysis in this study show that corporate governance has a significant effect on tax avoidance, while liquidity does not have a significant effect on tax avoidance with liquidity as the mediating variable.